Khawaja Yusuf Hamadānī: His Life, Thoughts and Contribution to the Contemporary Sufism - Mansurov, Fatkhiddin (Infonomics Society, 2016)
This study investigates the thoughts and contribution of prominent Sufi scholar Khawaja Yusuf Hamadānī (d. 535 H/1140). He played an important role in the formation of Sunni Sufism that had extended to our present time and nurturing great scholars of all times. He remained among the people, taught the religion of Islam to everyone without discrimination, guided and delivered his admonitions to his people in a proper way. Yusuf Hamadānī preferred these deeds over seclusion which was quite popular in the previous decades among Sufis. He has become one of the Sufi Masters with the most number of disciples and educated Sufi leaders such as Khawaja Abdulkhāliq Ghijduwānī (d. 575 H/1179) and Khawaja Ahmad Yasawī (d. 562 H/1166) being the founders of the two renowned Sufi orders the Khawajagan-Naqshbandiyya and Yasawiyya that played significant roles in upholding Sufism to the present days. The study is considered as one of the significant research works conducted on Yusuf Hamadānī’s life, teachings and his contribution to contemporary Sufi thought.